The Contribution of Achievement Motivation, Use of Information Technology, and Learning Outcomes of Creative Entrepreneurial Products on Interest in Entrepreneurship - Fitri Jalal; Muhammad Adri; Riki Mukhaiyar; Rajal Abdullah (STKIP Singkawang, 2025)
Entrepreneurship education in vocational high schools plays a crucial role in shaping students to become independent and innovative individuals capable of creating their own businesses. However, many students still show a low level of interest in entrepreneurship, which calls for an investigation into the influencing factors. This study aims to analyze the influence of achievement motivation and the use of information technology on students’ entrepreneurial interest, either directly or indirectly through entrepreneurial learning outcomes. The research was conducted using a quantitative correlational method involving 125 students from SMKN 2 Merangin during the 2024/2025 academic year. Data were collected through validated and reliable questionnaires measuring achievement motivation, technology use, and entrepreneurial interest. Students' learning outcomes were obtained from their average scores in the subject